Vertical Line Requirements and North Atlantic Right Whale Entanglement Risk Reduction for the Gulf of Maine American Lobster Fishery - Willse, Nathaniel; Summers, Erin; Chen, Yong (Marine and coastal fisheries, 2022)
In the U.S. western Atlantic Ocean, North Atlantic right whales Eubalaena glacialis are subject to gear entanglement in fixed‐gear vertical line fisheries, with mortality risk increasing with line strength and spatial density. U.S. federal management agencies have mandated vertical line strength limits (235.033‐kg‐m [1,700‐ft‐lb] breaking strength) to curtail the injury and mortality risk that entanglement poses to right whales. Limiting the strength of vertical lines used in the trap fishery for American lobster Homarus americanus, however, could negatively impact the economic resilience of New England fishing communities if it forces the purchase of new equipment or increases the incidence of break‐offs and lost gear. We provide a novel look at the spatially distinct vertical line strength requirements for the Maine American lobster trap fishery. The hauling load requirements of the fishery were modeled using measurements of strain put on vertical lines used in typical lobster trap operations to determine the minimum strength necessary to fish safely and avoid dangerous line breaks. New regulations on minimum trawl lengths (number of traps fished per vertical line) taking effect in 2022 will cause increases in lobster fishery vertical line loads across all fishing grounds, considerably increasing with depth and distance from shore. Our models indicated that inshore areas can be safely fished with vertical lines within the recommended whale‐safe 235.033‐kg‐m (1,700‐ft‐lb) breaking strength specification, whereas the offshore lobster fishery will need a suite of measures beyond line strength reductions to reduce entanglement risk and mortality of right whales. We provide guidelines for the minimum line strength necessary for fishery operations, which can be used to inform management goals that balance the need for a sustainable lobster fishery and the conservation of right whales.